O74: ASSESSING THE USEFULNESS OF THREE-DIMENSIONAL IMAGING AND VIRTUAL REALITY IN SURGICAL PLANNING: A MEDICAL STUDENT LED PILOT STUDY. (27th April 2021) - Ryan, C; O'Malley, E; Sheppard, D
Abstract: Introduction: Nephron-sparing surgery is becoming more common as surgical techniques advance. VR and 3D visualisation appear to provide better anatomical understanding in presurgical planning than two-dimensional alone. 3D models may enable greater tissue salvation and fewer complications. 3D model preparation and advancing research is expensive and time consuming. We aim to pilot study led by medical student, create reliable anatomical kidney models and assess usefulness in surgical planning. Method: Routine CT urograms were performed on 128 slice scanner using split bolus technique. Medical student segmented and displayed models in VR using 3DSlicer. Radiology registrar and consultant validated models. Two urology surgeons completed qualitative questionnaires. Result: We included two patients. Only minor segmentation tweaks by radiologist ensured accurately demonstrated tumors. Tissue contrast quality varied between CT scans complicating segmentation. Both surgeons deemed models helpful in visualising hilar anatomy, predicting bleeding complications, determining laparoscopic/open and partial/full nephrectomy approach. Surgeons prioritised vasculature visualisation over collecting system. Surgeons suggested gauging tumor depth would be useful. Considering 3D printing cost, surgeons agreed VR alone may suffice. Conclusion: Surgeons found 3D and VR enabled accurate surgical planning and patient counselling regarding nephrectomy risk. Minor CT protocol recommendations enable easier and more accurate segmentation, without increasing patient's radiation exposure. Annual leave during 8-week summer project reflects case numbers. Since, we've identified more cases to assess surgical parameters against matched cohort. We've begun work for adrenal surgery. It's feasible for medical students with minimal surgical/radiological knowledge to advance this research, gaining valuable experience. Abbrev: Virtual Reality(VR), Three-dimensional(3D), Computerised Tomography(CT) Take-home message: Three-dimensional imaging and virtual reality may improve surgical planning and patient counselling. Regarding nephrectomy, this could give surgeons the confidence to convert from full nephrectomy to partial nephrectomy approach, improving patient outcome.